THE EFFECT OF SELF-EFFICACY, WORK EXPERIENCE, AND COMMUNICATION ON EMPLOYEE PERFORMANCE AT PT IMA MONTAZ SEJAHTERA, LHOKSEUMAWE - Putria Zamharira Alisya; Nurmala; Ibrahim Qamarius; Sullaida (RADJA PUBLIKA, 2025)
This study investigates the impact of self-efficacy, work experience, and communication on employee performance at PT Ima Montaz Sejahtera, Lhokseumawe. Using quantitative methods and statistical analysis, the research examines the relationship between these variables. The results indicate that self-efficacy has a significant and positive effect on employee performance, suggesting that a strong belief in one's abilities enhances job performance. While work experience also shows a positive influence, its impact is not as statistically significant as self-efficacy. The study further reveals that effective communication within the organization plays a crucial role in fostering a positive work environment and improving employee outcomes. These findings highlight the importance of nurturing employee self-confidence and promoting clear, open communication channels to maximize productivity and success within the company.